2018
DOI: 10.1117/1.oe.57.2.023106
|View full text |Cite
|
Sign up to set email alerts
|

Focus measure method based on the modulus of the gradient of the color planes for digital microscopy

Abstract: , "Focus measure method based on the modulus of the gradient of the color planes for digital microscopy," Opt. Eng. 57(2), 023106 (2018), doi: 10.1117/1.OE.57.2.023106. Abstract. The modulus of the gradient of the color planes (MGC) is implemented to transform multichannel information to a grayscale image. This digital technique is used in two applications: (a) focus measurements during autofocusing (AF) process and (b) extending the depth of field (EDoF) by means of multifocus image fusion. In the first case,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In addition, in order to analyze and view the results more conveniently and intuitively, this study normalizes all the results, as shown in Figure 5 . The non-subsampled contourlet transform (NSCT), Tenengrad algorithm [ 29 ], Roberts algorithm [ 30 , 31 ], discrete cosine transform (DCT) [ 32 , 33 ], energy of gradient (EOG) [ 34 ] algorithm, Canny algorithm [ 35 , 36 ], and Laplacian algorithm [ 37 , 38 ] are selected for this comparative experiment. The Tenengrad algorithm uses a Sobel [ 39 , 40 ] operator to extract gradient values in horizontal and vertical directions, and then calculates the gradient square sum of all pixels.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in order to analyze and view the results more conveniently and intuitively, this study normalizes all the results, as shown in Figure 5 . The non-subsampled contourlet transform (NSCT), Tenengrad algorithm [ 29 ], Roberts algorithm [ 30 , 31 ], discrete cosine transform (DCT) [ 32 , 33 ], energy of gradient (EOG) [ 34 ] algorithm, Canny algorithm [ 35 , 36 ], and Laplacian algorithm [ 37 , 38 ] are selected for this comparative experiment. The Tenengrad algorithm uses a Sobel [ 39 , 40 ] operator to extract gradient values in horizontal and vertical directions, and then calculates the gradient square sum of all pixels.…”
Section: Resultsmentioning
confidence: 99%
“…However, the results also indicate that increasing the sizes of the filters for both RDF and DRDF leads to a greater deviation from the ground truth and, hence, results in a loss of details. Next, the proposed method was compared to seven focus computation methods, i.e., gray-level variance (GLV) [7], modulus of the gradient of the color channel (MCG) [13], modified-Laplacian (ML) [3], sum and spread focus measure (FMSS) [23], reduced Tenengrad (RT) [14], multi-scale-morphological focus measure (MSM) [24], and ring difference filter (RDF) [25]. For visual comparisons, we constructed depth maps of synthetic datasets, Antinous, Cotton, and Pens, using different methods, as shown in Figure 5.…”
Section: Comparative Analysismentioning
confidence: 99%
“…Tenengrad focus measure (TFM) is the most commonly used; it calculates the gradient of an image using the Sobel operator in both the x and y directions, and then sums up the squared magnitude of the gradient over a small window to obtain the sharpness value. Other common methods in this category include the local edge gradient analysis [12], modulus of the gradient of the color channel (MCG) [13], and reduced Tenengrad (RT) [14], which is a slight modification to the TFM. Second derivative-based focus measures utilize the Laplacian of an image.…”
Section: Introductionmentioning
confidence: 99%
“…In the proposed method, first, initial focus volume is obtained through the DRDF and then depth maps are computed from the enhanced focus volume through PFF. The performance of the proposed method is then thoroughly tested against five state-of-the-art methods: GLV [39], MCG [40], ML [24], FMSS [41], and RDF [34]. These five methods are applied to the five real data sets to obtain the focus volumes, and the depth maps are extracted by obtaining the image numbers having the best focus measures in the optical direction.…”
Section: Comparative Analysismentioning
confidence: 99%
“…For this, we selected the Buddha data set, as the images in this data set contain a significant amount of noise. Depth maps obtained from the comparative methods GLV [39], MCG [40], ML [24], FMSS [41], RDF [34], and the proposed method are shown in Figure 7. From the figure, it can be observed when the depth map was extracted; every method except ours found it challenging to counter noise.…”
Section: Comparative Analysismentioning
confidence: 99%